2022
DOI: 10.1111/jocd.14701
|View full text |Cite
|
Sign up to set email alerts
|

The comparative in vitro killing activity of tea tree oil versus permethrin on Demodex folliculorum of rosacea patients

Abstract: Background Demodex mites have been implicated in several cutaneous disorders compelling the research efforts for effective anti‐Demodex therapy. Objective Compare the survival time (ST) of Demodex folliculorum exposed to six different concentrations of tea tree oil (TTO) versus a positive control (permethrin 5%) and a negative control (immersion oil) group. Materials and methods The wastes of rosacea patients’ standardized superficial skin biopsy samples were recruited for the trial. The primary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…A previous study showed the mean ST of Demodex mites in permethrin 5% was 12.5 ± 1.9 min, while the mean ST in permethrin 1% was 47.2 ±12.3 min (in this trial) which led to the conclusion that permethrin has a dose-related acaricidal effect. 27 …”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed the mean ST of Demodex mites in permethrin 5% was 12.5 ± 1.9 min, while the mean ST in permethrin 1% was 47.2 ±12.3 min (in this trial) which led to the conclusion that permethrin has a dose-related acaricidal effect. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Acaricidal effect of TTO and its components against mites. Fifty-five studies targeted mites, which include Demodex mites (n = 44) [52,56,58,59,[61][62][63][64][69][70][71][72][73][74][75][76][77][78][79]81,82,85,[87][88][89][90][91][92][93][94][97][98][99][100][101][102][107][108][109]112,114,117,120,121], scabies mites (n = 5) [57,86,113,118,119], and house dust mites (n = 6) (Tables 1-5)…”
Section: Qualitative Synthesesmentioning
confidence: 99%
“…Among 44 studies involving Demodex mites, six were in vitro studies [64,70,71,100,112,114], two studies followed a mixed in vitro/clinical approach [81,97], and 36 were clinical studies (14 RCTs [56,62,63,72,74,77,85,88,92,93,107,108,120,121] and 22 non-RCTs [52,58,59,61,69,73,75,76,78,79,82,87,[89][90][91]94,98,99,101,102,109,117]) (Tables 1 and 2).…”
Section: Demodex Mitesmentioning
confidence: 99%
See 2 more Smart Citations